Adolescents Voice their Needs: Implications for Health Promotion and Suicide Prevention - Collins, Sandra; Angen, Maureen (Canadian Journal of Counselling and Psychotherapy, 2007)
Adolescents' self-perceived need for health-related services, instruction, and environmental changes were investigated. Significant differences were observed between students classed as high and lower risks for suicide and between minority and majority adolescents. Needs in the area of counselling services, services related to sexuality, and interpersonal relationships were priorities for high risk minority students suggesting the need for specific programming targeting these students. For both minority and majority high risk students, educational and career foci paled in comparison to personal and interpersonal struggles, indicating that systemic and group-specific health promotion initiatives may be essential prerequisites to meeting traditional educational mandates.